2020
DOI: 10.3389/fvets.2020.579933
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and Adjunctive Therapies for Spinal Cord Injury Following Acute Canine Intervertebral Disc Herniation

Abstract: Some dogs do not make a full recovery following medical or surgical management of acute canine intervertebral disc herniation (IVDH), highlighting the limits of currently available treatment options. The multitude of difficulties in treating severe spinal cord injury are well-recognized, and they have spurred intense laboratory research, resulting in a broad range of strategies that might have value in treating spinal cord-injured dogs. These include interventions that aim to directly repair the spinal cord le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 140 publications
0
11
0
1
Order By: Relevance
“…Several investigations have reported that multimodal approaches may facilitate motor recovery and are useful in improving the outcome, in combination with additional approaches directed to the lesion epicenter [ 2 , 111 , 112 , 113 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations have reported that multimodal approaches may facilitate motor recovery and are useful in improving the outcome, in combination with additional approaches directed to the lesion epicenter [ 2 , 111 , 112 , 113 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…4-AP is a potassium channel antagonist that may improve hindlimb motor function in chronic thoracolumbar spinal cord dogs [ 81 , 114 , 127 ]. This beneficial effect could be achieved through the enhancement of central conduction by anatomically intact axons traversing the injury site, as well as direct synaptic effects [ 29 , 128 , 129 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been investigations regarding pharmacological management with 4-AP in thoracolumbar chronic SCI dogs to improve neurological deficits [ 51 , 52 , 53 ]. The 4-AP is a potassium channel antagonist that could be used to block exposed fast-gated potassium channels in demyelinated axons and increase synaptic transmission at the pre-synaptic level [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts to alleviate SCI symptoms by local or systemic stem cell application have led to mixed results with little or no relevant clinical benefit so far. [8][9][10] More encouraging therapeutic effects result from approaches that aim at locomotor restoration by activating spinal locomotor circuits that are deprived from cortical input in SCI. In this context, promising experimental results have been reported from a combination of electrical stimulation and intraspinal pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although strong research efforts have been made to improve sensorimotor functions of SCI patients, therapeutic options for these patients are still very limited. Various attempts to alleviate SCI symptoms by local or systemic stem cell application have led to mixed results with little or no relevant clinical benefit so far 8–10 . More encouraging therapeutic effects result from approaches that aim at locomotor restoration by activating spinal locomotor circuits that are deprived from cortical input in SCI.…”
Section: Introductionmentioning
confidence: 99%